2015
DOI: 10.1016/j.jmp.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

From Uniform Expected Utility to Uniform Rank-Dependent Utility: An experimental study

Abstract: This paper presents an experimental investigation of the Uniform Expected Utility (UEU) criterion, a model for ranking sets of uncertain outcomes. We verified whether the two behavioral axioms characterizing UEU, i.e., Averaging and Restricted Independence, are satisfied in a pairwise choice experiment with monetary gains. Our results show that neither of these axioms holds in general. Averaging in particular, appears to be violated on a large scale. On the basis of the current study and a previous one, we can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It seems unlikely that such a news would increase (even weakly) the attractiveness of the treatment from the patient's point of view. Vridags and Marchant (2015) have shown that the very fact of ruling out both forms of extremism from the part of a RDWAU decision maker-a requirement referred to as dominance in (Barberà, Bossert, and Pattanaik, 2004)-leads to a significant restrictions of the rank dependent weights used by him or her when evaluating decisions with different numbers of outcomes. Specifically, the following Proposition is proved in Vridags and Marchant (2015) (Proposition 1) (with mild changes in the notation and definition).…”
Section: Extreme Optimism and Pessimismmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems unlikely that such a news would increase (even weakly) the attractiveness of the treatment from the patient's point of view. Vridags and Marchant (2015) have shown that the very fact of ruling out both forms of extremism from the part of a RDWAU decision maker-a requirement referred to as dominance in (Barberà, Bossert, and Pattanaik, 2004)-leads to a significant restrictions of the rank dependent weights used by him or her when evaluating decisions with different numbers of outcomes. Specifically, the following Proposition is proved in Vridags and Marchant (2015) (Proposition 1) (with mild changes in the notation and definition).…”
Section: Extreme Optimism and Pessimismmentioning
confidence: 99%
“…Hence, a pessimistic patient who gives more weights to the samples where the treatment performs poorly to those where it performs well could very well choose the third treatment over the second even though he has chosen the first treatment over the second. In the only instance we know where the averaging axiom has been tested in an experimental context (Vridags and Marchant, 2015), it has been rejected by a vast majority of subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation